Análise comparativa da resistência de união entre sistemas ceramocerâmicos e metalocerâmico - Silva Neto, Genilson da (2011)
The aim of this study was to perform quantitative and qualitative characterization of metalloceramic and ceramic interfaces commercially available in the market for dental purposes. For this, cylindrical patterns (6.5 mm in height x 6 mm in diameter) were fabricated and divided into 10 groups: Wiron 99/Kiss (WK), In-Ceram Zirconia/Vita VM7 (ICZ-VM7), Ceramill White Core Zirconia/Nobel Rondo and Nobel Rondo Press (CWCZ-NR and CWCZNRP); Ceramill Colored Core Zirconia/Nobel Rondo and Nobel Rondo Press (CCCZ-NR and CCCZ-NRP), Procera White Core Zirconia/ Nobel Rondo and Nobel Rondo Press (PWCZ-NR and PWCZ-NRP); Procera Colored Core Zirconia/Nobel Rondo and Nobel Rondo Press (PCCZ-NR and NRP). All groups were submitted to a shear bond strength test until fracture (quantitative) and SEM/EDS (qualitative analysis). Mean shear values (MPa) were: WK (36.12±3.86); ICZ-VM7 (34.20±5.85); CWCZ-NR and NRP (33.69±8.75 and 51.44±7.39); CCCZ-NR and NRP (36.00±9.05 and 36.52±3.77); PWCZ-NR and NRP (48.23±7.32 and 46.50±10.87); PCCZ-NR and NRP (37.16±8.37 and 28.35±9.21). MEV(EDS,EDR) and EDRX characterization determined cohesive fractures in both WK and ceramic groups, except on the PWCZ-NR group, wich showed mixed fractures with small crest and islets of veneering material. All ceramic interfaces provided shear bond strength values near to that control group. However, groups PWCZ-NR and NRP showed superior values.